Energy Economics and Policy of Renewable Energy Sources in the European Union - Strielkowski, Wadim; KrÅ¡ka, Å tÄ›pÃ¡n; Lisin, Evgeny (International Journal of Energy Economics and Policy, 2013)
European Union adapted the policy of reducing its carbon footprint and embarked on the journey to shift to renewable energy sources in the early 1990s. The whole process started with implementations of binding rules that set up indicative targets for the EU Member States. However, this process had to go hand in hand with high energy costs charged to the consumers. This paper defines various types of renewable sources in the EU and analyses European legislation on renewable energy sources. In addition, it deals with the current situation regarding the energy policies in the European Union and outlines its main criticisms and prospects. The results and conclusions might be of some value for EU main energy providers as well as for the EU partners in the world. Keywords: Energy economics; renewable energy; energy providers; economic forecasting; EU JEL Classifications: F40; F50; Q20; Q47